Holography-guided procedural planning for modifying Venus P-valve implantation technique in patients with left pulmonary artery stents: a case-series - d’Aiello, Angelo Fabio; Schianchi, Laura; Bevilacqua, Francesca; Ferrero, Paolo; Micheletti, Angelo; Negura, Diana Gabriela; Pasqualin, Giulia; Chessa, Massimo (Frontiers in Cardiovascular Medicine, 2024)
Background: Venus P-valve TM (Venus Medtech, Hangzhou, China) is a self-expandable bioprosthetic valve that can be transcatheter-implanted in native right ventricular outflow tract (RVOT) patients. Valve implantation is technically challenging. Due to the implantation technique, left pulmonary artery (LPA) stents represent a relative contraindication to Venus P-valve. In this case series, we describe our experience in implanting Venus P-valve in patients with previous LPA stents and the use of holographic models to facilitate procedural planning.From January to October 2023, 17 patients were scheduled for Venus P-Valve implantation. 16/17 (94%) patients were successfully implanted. 3/16 (18,7%) patients underwent Venus Pvalve implantation with LPA stents. All patients underwent pre-operative CT scan. CT data set were employed to create three-dimensional (3D) holographic models (Artiness, Milan, Italy) of the entire heart, which were useful to plan valve implantation with a modified technique. Procedural success rate was 100%.No procedural complications occurred. All three patients presented good haemodynamic and angiographic results at discharge and follow-up visits.This case-series underscores the feasibility of Venus P-valve implantation in patients with previous LPA stents. The use of holographic models facilitated procedural planning in these challenging anatomical scenarios.